OPTIMALISASI PARAMETER TEKNIK PENGELASAN FLUX CORED ARC WELDING (FCAW) MENGGUNAKAN METODE TAGUCHI MULTIRESPON PCR-TOPSIS - Kusumawardani, Meilia; Mustafid, Mustafid; Yasin, Hasbi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Multi response optimization case has encountered in industrial. Multirespon Taguchi TOPSIS PCR method is used to determine the optimal combination of factors/level and calculate the optimum performance for each response. Purpose of Taguchi method is to reduce the variability, and theory Process Capability Ratio (PCR) shows the process situation in which the parts produced are good or defective. Then Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) to determine the optimal combination multi response case. The case study using the technique of Flux Cored Arc Welding welding (FCAW) using characteristic larger is better. Performance optimal conditions for factor Welding current at 280 ampere and factor Electrode stickout at 21 mm. Then optimal performance conditions for each responses are hardness=481.145 and deposition rate=3.813. These results have a higher value when compared with the initial conditions. So the case results meet the characteristics of larger is better. Keywords : Taguchi Method, PCR, TOPSIS, FCAW